Strengthening Chile's Rule-Based Fiscal Framework - Daban Sanchez, Teresa (IMF Working Papers; Working Paper ;, 2011)
The cornerstone of Chile's impressive fiscal performance has been its structural balance rule. By insulating public spending from short-term copper price fluctuations and the business cycle, the rule has helped preserve fiscal discipline. However, the implementation of the rule in recent years has revealed certain challenges, and in May 2010, the government established a high-level commission to recommend reforms that could make the rule even more effective. This paper assesses the scope for improving the design and implementation of the structural balance rule in light of best practices and OECD country experience with fiscal rules. This assessment suggests several options to strengthen Chile's fiscal rule, including by simplifying the calculation of the structural balance; enhancing the rule's flexibility, transparency and accountability; and complementing it with a medium-term fiscal framework.